PENGARUH KOMPETENSI KEWIRAUSAHAAN KEPALA SEKOLAH TERHADAP PENGEMBANGAN PROGRAM KEWIRAUSAHAAN DI SEKOLAH MENENGAH KEJURUAN (SMK) SE-BANJARMASIN - Rani, Tri; Ratumbuysang, Monry Fraick Nicky Gillian; Hasanah, Mahmudah; Rizky, Maulana (JURNAL ILMIAH EDUNOMIKA, 2024)
This research aims to determine the influence of school principals' entrepreneurial competence in developing entrepreneurship programs in Vocational High Schools (SMK) throughout Banjarmasin. The population used in this research was all principals in vocational schools. The sampling method is using non-probability sampling techniques. The type of nonprobability sampling used is saturated sampling. The sampling method obtained 20 samples. This research uses quantitative research. The analysis used is simple linear regression analysis, with t test and coefficient of determination. The Principal Entrepreneurial Competency variable of 0.501 states that every time there is an increase in the Principal's Entrepreneurial Competency by 1%, the Entrepreneurship Program (Y) will increase by 0.501. This means that the principal's entrepreneurial competency variable has Sig. Amounting to 0.005 < 0.05, it can be concluded that the principal's entrepreneurial competency variable has a significant effect on the entrepreneurship program. the contribution of creating innovation, working hard, having strong motivation, never giving up, and having entrepreneurial instincts towards the entrepreneurship program was 36.6% while the remaining 63.4% was influenced by other variables not examined in this research. This proves that there is an influence between the principal's entrepreneurial competency on the Entrepreneurship Program.